Uninvited Guests: Dissecting Treaty Shopping in Commercial Diplomacy - Djigsa, Wakgari (Hasanuddin Journal of International Affairs, 2025)
This research objective is to explain the use of treaty shoping ini commercial diplomacy today.  Nowdays the foreign investors resort to treaty shopping, by which they require host countries to perform unintended obligations. Treaty shopping allows foreign investors to find some connecting factors with the third country BIT concluded with the host country, by disregarding the BIT their home country concluded with that specific host country to find more protection for their investments.  is a very serious problem for the host countries. Against this backdrop, this article critically analyzes the approaches of dissecting treaty shopping in commercial diplomacy. Investment agreements are used as primary source of data while literatures and reports are relied upon as secondary source of data. The article identifies the magnitude of challenges faced especially by host countries in concluding and implementing investment agreements. It recommends States to be curious and properly utilize the art of negotiation in their commercial diplomacy.